2019
DOI: 10.7759/cureus.5810
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and Risk of Osteoporotic Fractures: A Meta-Analysis

Abstract: IntroductionInflammatory bowel disease (IBD) and its complications have been well-established. The literature shows an association between IBD and decreased bone mineral density in the adult population. However, most studies have reported an association between IBD and osteoporosis, while the risk of fractures has not been well-studied. The aim of this meta-analysis is to summarize the best available evidence regarding IBS and osteoporotic fractures.MethodsA review of the literature using the MEDLINE and EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Moreover, studies estimated that as many as 77% of patients with IBD have osteopenia and 12–41% have osteoporosis [ 41 , 45 ]. The risk of osteoporosis and osteopenia among patients with IBD is also related to insufficient intake and absorption of calcium and potassium, lower body mass index (BMI) and insufficient physical activity, low peak bone mass, and certain medications, especially glucocorticosteroids [ 46 , 47 ]. Adequate calcium intake is crucial due to IBD’s association with an increased incidence of osteoporosis, and additionally, during ongoing inflammation, pro-inflammatory cytokines affect the activity of bone cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies estimated that as many as 77% of patients with IBD have osteopenia and 12–41% have osteoporosis [ 41 , 45 ]. The risk of osteoporosis and osteopenia among patients with IBD is also related to insufficient intake and absorption of calcium and potassium, lower body mass index (BMI) and insufficient physical activity, low peak bone mass, and certain medications, especially glucocorticosteroids [ 46 , 47 ]. Adequate calcium intake is crucial due to IBD’s association with an increased incidence of osteoporosis, and additionally, during ongoing inflammation, pro-inflammatory cytokines affect the activity of bone cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cochran's Q test and I2 statistic were used to determine the between-study heterogeneity. A value of I2 of 0%-25% represents insignificant heterogeneity, greater than 25% but less than or equal to 50% represents low heterogeneity, greater than 50% but less than or equal to 75% represents moderate heterogeneity, and greater than 75% represents high heterogeneity [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Early detection and lifestyle modification could potentially decrease the risk of osteoporosis and hence the fractures in patients with CLD. This work has been presented as an abstract [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased bone mineral density (BMD) could lead to fragility fractures. In a recent meta-analysis, Hidalgo 2 found that patients with IBD have a 32% increased risk of developing an osteoporotic fracture, more commonly in the vertebral area 3 .…”
Section: Introductionmentioning
confidence: 99%